Understanding and troubleshooting Cisco Catalyst 9800 Series wireless controllers - Arena, Simone; Darchis, Nicolas; Crippa, Francisco Sedano; Katgeri, Sudha (Cisco Press, 2023)
The definitive professionals guide to the Cisco next-gen 9800 wireless controllers. As wireless networks, applications, and services rapidly evolve, they grow increasingly business critical, with steeper requirements for performance, latency, deployment density, and device support. The advanced Catalyst 9800 wireless controllers from Cisco meet these challenges, delivering exceptional adaptability, security, performance, scalability, and programmability. Based on the modern and secure Cisco IOS XE operating system, their support for Cisco intent-based networking will help you continually leverage new innovation. Now, four Cisco experts offer end-to-end guidance, practical tips, and proven recommendations for designing, deploying, and managing wireless networks with the Catalyst 9800. For technical decision makers, this guide delivers a deep understanding of Catalyst 9800 hardware and software, tightly linked to business value. Architects will find essential details for both upfront network design and feature implementation. Network operators and other IT professionals will discover tested tools and methods for reliable and efficient setup, configuration, monitoring, and troubleshooting. Whatever your role, this guide will help you maximize the value of any Catalyst 9800 network, and serve as your indispensable reference for years to come.
Includes index
Keywords: Wireless LANs; Réseaux locaux sans fil